Flow Induced Vibration of Simply Supported Cantilever Beam based on One-way Fluid Structure Interaction - Mohamad Faizal, Nazren Al Nazirul; Zaman, Izzuddin (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Vibration problems occur in many structural buildings and piping systems as a result of fluid flow. This is because fluid flow is an energy source that capable of generating structural and mechanical oscillations. The most accurate description to describe these interaction between the fluid's dynamic forces and elastic forces of a structure is flow-induced vibration. In these study, a flow-induced vibration of simply supported cantilever beam was investigated based on one way fluid structure interaction (FSI). Ansys Workbench was used to simulate the dynamic behaviour of the beam when subjected to air flow. There are two beam angle positions analysed at 60° and 90° vertically, where each beam was exposed to two different fluid flow rates of 10 and 15 m/s. Transient structural, modal analysis, harmonic analysis and fluid fluent were among the analyses used in the study. Simulation results show that the overall value of a 90° beam orientation in fluid pressure, velocity, total deformation, von-mises stress, and frequency response is higher than a 60° beam orientation. This shows that beam orientation significantly affects vibration level. Higher vibration levels also affect fluid flow speed and type. As the surface area of the beam struck by the fluid flow increases, so will the overall value of the beam's fluid pressure, velocity, total deformation, Von-Mises stress, and frequency response. In this case, the 90° beam orientation has more surface area where the fluid flow strikes than the 60° beam orientation.